Design Parameters of Cycloidal Gear Reducers Considering Strength Conditions and Meshing Correction - Warda, Bogdan; Batory, Damian; Grzegorz Mitukiewicz (Wydawnictwo Politechniki Łódzkiej, 2025)
Cycloidal gear reducers, commonly referred to as Cyclo drives, provide an alternative to traditional involute gear systems. They offer high torque density, compactness and precision. This paper presents a strength-based design methodology for cycloidal reducers, deriving key geometric parameters directly from load conditions and material properties rather than relying solely on geometric assumptions. A Hertzian contact stress model is used to determine the minimum diameter of the roller ring, ensuring durability and structural integrity. Correction factors are introduced to address manufacturing tolerances and assembly constraints, providing design guidelines that can be applied in practice. Furthermore, the study explores meshing correction in cycloidal gears, emphasising its critical role in ensuring proper operation. Analytical and numerical methods are employed to evaluate load distributions in rolling elements, focusing particularly on the impact of the roller radius and meshing correction parameters on contact pressures and the number of engaged teeth. The proposed approach bridges the gap between theoretical modelling and engineering practice, enabling the efficient preliminary design of cycloidal gear systems, reducing the need for iterative trial and error, and improving their reliability. The results highlight the potential of this methodology for wider industrial applications, particularly in robotics, automation and heavy-duty machinery, where compact, precise and durable transmission solutions are required.
Keywords: cycloidal gear reducer; contact stress analysis; meshing correction; strength-based design